Analisis Probability Distribution Function Terhadap Perubahan Tutupan Lahan Dan Fraksi Awan Di Indonesia - Jeddah Yanti; Chian-Yi Liu; Togi Tampubolon (Universitas Muslim Indonesia, 2022)
Land use exceeds the standard of suitability and availability over Indonesia, which causes uncontrolled land acquisitions every year. Changes in land use can be controlled by monitoring changes in land cover and the effect of land changes on hydrological cycle components such as cloud fraction. The land cover and cloud fraction distribution were identified using the NDVI index and cloud fraction parameters. The NDVI index value in Indonesia is 0.73 to 0.81, representing land cover in Indonesia, which is relatively high. Meanwhile, the cloud fraction showed the lowest value between 0.6 to 0.7 in summer and experienced the highest cloud cover at the peak of the rainy season. The analysis of the distribution of both land cover and cloud cover shows the consistency of value stability in the rainy season starting from November to May from 2003 to 2016. The correlation value based on the spatial analysis between the NDVI anomaly and the cloud fraction parameter anomaly has a value range of around -0. 8 to 0.8. The correlation between the NDVI anomaly and the cloud parameter anomaly has a negative correlation in Indonesia, including Sumatra, Kalimantan, Java and Bali, Sulawesi, Nusa Tenggara, Maluku, and Papua. Sumatra, Kalimantan, and Papua islands have a prominent role with a negative correlation between the NDVI anomaly and the cloud fraction parameter anomaly. It is feared to be caused by changes in land use to deforestation of natural area conservation areas into oil palm plantations and mining.